1990
DOI: 10.1063/1.458523
|View full text |Cite
|
Sign up to set email alerts
|

The thermal conductivity of ethane in the critical region

Abstract: The thermal conductivity of ethane in the critical region has been measured isochorically at densities up to 1.76 times the critical density and at temperatures down to 0.13 K above the critical temperature. The measurements were performed with a thermal conductivity apparatus based on the parallelplate method. The experimental accuracy was 0.5 to 5 %, depending on the distance to the critical point. The experimental results agree well with a recently developed crossover theory for the thermal diffusivity of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 17 publications
0
71
1
Order By: Relevance
“…Thus, it is possible to examine some of the available experimental data in the light of the most modern theory and to confirm the internal consistency of various sets of experimental data. Furthermore, in the zero-density limit and around the critical point, theoretical studies have suggested acceptable functional forms for the representation of experimental data [2,14]. In order to perform such an analysis one must make use of experimental data over as wide a range of thermodynamic states as possible.…”
Section: Q(p T) = Qo( T) + Aq( P T) + a Cq(p T)= ~(P T) + Z~q(pmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible to examine some of the available experimental data in the light of the most modern theory and to confirm the internal consistency of various sets of experimental data. Furthermore, in the zero-density limit and around the critical point, theoretical studies have suggested acceptable functional forms for the representation of experimental data [2,14]. In order to perform such an analysis one must make use of experimental data over as wide a range of thermodynamic states as possible.…”
Section: Q(p T) = Qo( T) + Aq( P T) + a Cq(p T)= ~(P T) + Z~q(pmentioning
confidence: 99%
“…For this purpose Eq. (9) can be rewritten in terms of the first-density contribution and higher-density contributions, zlhr/, as A~l=blp+Ah~l=btp+ ~ bip i (14) i=2 …”
Section: Density Dependencementioning
confidence: 99%
“…The transport properties of a pure fluid show an enhancement in the region of the critical point, which has been observed experimentally for a number of fluids [23][24][25]. Although for viscosity the critical enhancement is weak and covers a small region, the critical enhancement of the thermal conductivity is observed in a large range of temperatures and densities.…”
Section: Excess Transport Propertiesmentioning
confidence: 83%
“…This behavior can be described by models that produce a smooth crossover from the singular behavior of the thermal conductivity asymptotically close to the critical point to the residual values far away from the critical point [30,45,54]. The densitydependent terms for thermal conductivity can be grouped according to Eq.…”
Section: Residual Thermal Conductivitymentioning
confidence: 99%
“…The theoretically-based crossover model proposed by Olchowy and Sengers [30,45,54] is complex and requires the solution of a quartic equation in terms of complex variables. A simplified crossover model has also been proposed by Olchowy and Sengers [32].…”
Section: Critical Enhancementmentioning
confidence: 99%